1995
DOI: 10.1161/01.hyp.26.6.1154
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Potentiates the Hypotensive Effect of Bradykinin in Conscious Rats

Abstract: Treatment with angiotensin-converting enzyme inhibitors increases the angiotensin-(1-7) [Ang-(1-7)] and bradykinin concentrations in plasma and tissue. In this study we evaluated the interaction between these peptides by determining the effect of Ang-(1-7) on the hypotensive action of bradykinin in conscious rats. Administration of Ang-(1-7) (5 nmol) did not change mean arterial pressure or heart rate. However, the hypotensive effect of bradykinin, produced by an intravenous or intra-arterial route, was potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
1
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 31 publications
5
100
1
5
Order By: Relevance
“…This BK-potentiating effect of Ang-(1-7) may contribute for its cardiovascular effects in normotensive (Paula et al 1995, Oliveira et al 1999, Greco et al 2006 and hypertensive (Lima et al 1997, Fernandes et al 2001 rats. Several mechanisms have been proposed to explain the BK-potentiating activity of Ang-(1-7), including ACE inhibition since Ang-(1-7) is an ACE substrate (Li et al 1997, Tom et al 2001, allosteric changes in ACE (Erdos et al 2002), and Mas-mediated changes in the BK signaling (Paula et al 1995, Oliveira et al 1999, Fernandes et al 2001, Ferreira et al 2001. In addition, vascular Ang-(1-7) actions could involve modulation of vascular effects of Ang II (Roks et al 1999, Stegbauer et al 2004.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 93%
“…This BK-potentiating effect of Ang-(1-7) may contribute for its cardiovascular effects in normotensive (Paula et al 1995, Oliveira et al 1999, Greco et al 2006 and hypertensive (Lima et al 1997, Fernandes et al 2001 rats. Several mechanisms have been proposed to explain the BK-potentiating activity of Ang-(1-7), including ACE inhibition since Ang-(1-7) is an ACE substrate (Li et al 1997, Tom et al 2001, allosteric changes in ACE (Erdos et al 2002), and Mas-mediated changes in the BK signaling (Paula et al 1995, Oliveira et al 1999, Fernandes et al 2001, Ferreira et al 2001. In addition, vascular Ang-(1-7) actions could involve modulation of vascular effects of Ang II (Roks et al 1999, Stegbauer et al 2004.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 93%
“…In addition, Ang-(1-7) amplifies the vasodilator actions of bradykinin (BK). 23 Additional evidence suggests that Ang-(1-7) reduces the release of norepinephrine acting through a BK/ nitric oxide-mediated mechanism that stimulates cGMP/ protein kinase G signaling. 24 Other experiments also point to an interrelationship between Ang-(1-7) and the prostaglandin-BK-nitric oxide system.…”
Section: Formation and Functions Of Ang-(1-7)mentioning
confidence: 99%
“…To determine the interaction of Ang-(1-7) and NO, studies conducted from our group confirmed that the vasodilator response was mediated by NO-but it was discovered that inhibition of NO synthase in 2-kidney-1-clip (2K1C) hypertension induced in dogs resulted in a blunted vasodilatory response, suggesting that an impairment in the NO system may play a role in the pathology of hypertension (Nakamoto et al 1995). Moreover, Ang-(1-7) potentiated the vasodilatory effect of bradykinin administered to conscious rats, and this response was significantly attenuated by indomethacin, suggesting the involvement of prostaglandins (Paula et al 1995). This effect was later confirmed by us, and we showed that this effect of Ang-(1-7) to potentiate bradykinin-induced vasodilation was due to the ability of Ang-(1-7) to inhibit ACE activity and release NO (Li et al 1997), thereby decreasing the metabolism of bradykinin and further stimulating vasodilation.…”
Section: Vascular Effects Of Ang-(1-7)mentioning
confidence: 99%